Purchasing power parity for developing and developed countries: what can we learn from non-stationary panel data models? - Imed Drine; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2008)
The aim of this paper is to apply recently developed panel cointegration techniques proposed by Pedroni (1999, 2004) and generalized by Banerjee and Carrion-i-Silvestre (2006) to examine the robustness of the PPP concept for a sample of 80 developed and developing countries. We find that strong PPP is verified for OECD countries and weak PPP for MENA countries. However in African, Asian, Latin American and Central and Eastern European countries, PPP does not seem relevant to characterize the long-run behavior of the real exchange rate. Further investigations indicate that the nature of the exchange rate regime doesn't condition the validity of PPP which is more easily accepted in countries with high than low inflation.
Keywords: E31; F0; F31; C15; 330; purchasing power parity; real exchange rate; developed country; developing country; panel unit-root and cointegration tests; Kaufkraftparität; Wechselkurssystem; Panel; Kointegration; Industriestaaten; Entwicklungsländer; OECD-Staaten